How peer coaching can contribute to doctors’ development as clinical supervisors: an interview study - Erik Myrberg; Maria Henningsson; Catharina Tennerhed; Mats Wahlqvist; Matilda Liljedahl (BMC Medical Education)
Abstract Purpose Clinical supervisors work in demanding, complex environments, and faculty development activities should prepare them for these challenges. This study investigated peer coaching in the clinical setting as a faculty development activity for clinical supervisors. The study aimed to explore how peer coaching is enacted and how peer coaching may support clinical supervisors’ development. Methods A realist evaluation study was conducted, involving qualitative interviews with 14 doctors who had participated in a peer coaching activity. Data were analyzed using a realist-informed reflexive thematic analysis. Results Themes that describe the conditions, learning behaviors, and potential learning outcomes of peer coaching were developed. A necessary condition for effective peer coaching was “Practicing supervision under safe circumstances.” Peer coaching was characterized by “Exploring a teaching strategy,” “Handling authentic complexity,” “Reflecting during observation,” “Receiving credible feedback,” and “Contrasting educational situations.” Potential outcomes included an increased “Awareness of the student’s perspective” and that “Supervision becomes a shared concern.” Conclusion The feedback component of peer coaching appears to support learning primarily by promoting reflective observation and initiating open, collegial discussions. Peer coaching can be conceptualized as reciprocal direct observation and discussions between equal colleagues, with mutual learning as the primary purpose. The contextually relevant influences on psychological safety are key factors to consider in implementing successful peer coaching. Clinical trial number Not applicable.